PEMBELAJARAN SEJARAH DI SEKOLAH PERBATASAN INDONESIA-MALAYSIA (STUDI KASUS DI SMP NEGERI 4 PALOH) - Superman Superman (Khazanah Pendidikan, 2015)
This research aims to; (1) describe the history lesson planning, (2) describe the process of teaching history, (3) describe the evaluation of the teaching of history and (4) analyzing constraints experienced in the process of teaching history. This research was conducted in SMP Negeri 4 Paloh. This research method is descriptive qualitative strategy used is a single case study. Results of this study concluded that: (1) Planning historical study conducted by social studies teacher at SMPN 4 Paloh still not optimal. The teacher has not made a good learning tool. Teachers have not been applying the concept of the learning plan in accordance with the demands of the curriculum. (2) The implementation of the teaching of history in SMP Negeri 4 Paloh still conventional. In teaching, teachers use a monotonous lecture method, less innovative learning media. Learning scenarios implemented without grooves so that there are no clear stages in its implementation. Material presented teacher absolute only obeying the groove and arrangement contained in the book. (3) social studies teacher not perform an adequate evaluation of learning. The evaluation process conducted merely making students grades. Capturing the value is only used for determining the grade. (4) Obstacles encountered in the process of teaching history in SMP 4 Paloh are limited facilities and infrastructure both at school and in the community. Keywords: History of Education, school borders, SMP Negeri 4 Paloh.